The effects of probiotic supplementation on mental health, biomarkers of inflammation and oxidative stress in patients with psychiatric disorders: A systematic review and meta-analysis of randomized controlled trials. (March 2020) - Amirani, Elaheh; Milajerdi, Alireza; Mirzaei, Hamed; Jamilian, Hamidreza; Mansournia, Mohammad Ali; Hallajzadeh, Jamal; Ghaderi, Amir
Highlights: Probiotic supplementation on mental health in psychiatric disorders was evaluated. Probiotic supplementation improved mental health. Probiotic supplementation decreased inflammatory markers. Abstract: Background and objective: In the current meta-analysis of randomized controlled trials (RCTs), the effects of probiotic supplementation on mental health, biomarkers of inflammation and oxidative stress in patients with psychiatric disorders were assessed. Methods: The following databases were search up to February 2019: PubMed, Scopus, Web of Science, Google scholar and Cochrane Central Register of Controlled Trials. Results: Twelve studies were included in the current meta-analysis. The findings demonstrated that probiotic supplementation resulted in a significant reduction in Hamilton Depression Rating Scale (HAMD) [Weighted Mean Difference (WMD): -9.60; 95 % CI: -10.08, -9.11]. In addition, a significant reduction in C-reactive protein (CRP) (WMD: -1.59; 95 % CI: -2.22, -0.97), interleukin 10 (IL-10) (WMD: -0.29; 95 % CI: -0.48, -0.11) and malondialdehyde (MDA) levels (WMD: -0.38; 95 % CI: -0.63, -0.13) was found after probiotics supplementation. No significant change was seen in Beck Depression Inventory (BDI) score (WMD: -11.17; 95 % CI: -24.99, 2.65), tumor necrosis factor-α (TNF-α) (WMD: -0.12; 95 % CI: -0.20, -0.05), IL-1B (WMD: -0.34; 95 % CI: -1.43, 0.74), IL-6 (WMD: 0.03; 95 % CI: -0.32, 0.38), nitric oxide (NO) (WMD: -0.54; 95 % CI: -2.16, 1.08), glutathione (GSH) (WMD: 46.79; 95 % CI: -17.25, 110.83) and total antioxidant capacity (TAC) levels (WMD: 15.21; 95 % CI: -59.96, 90.37) after probiotics supplementation. Conclusion: Overall, the current meta-analysis demonstrated that taking probiotic by patients with psychiatric disorders had beneficial effects on HAMD, CRP, IL-10 and MDA levels, but it did not affect BDI score, other markers of inflammation and oxidative stress.